Historical overview of the dementia syndrome's emergence and evolution - Eslaidi Mendoza Clavel; Juana Adela Fong Estrada; Ariadna Céspedes Moncada (Medisur)
Dementia is a syndrome usually of a chronic and progressive nature, in which there is an alteration of multiple higher cortical functions. This disease generates great bio-psycho-social concern, as well as being the most costly disease faced by health services, and having a considerable impact on the family and on society worldwide. The first phenomenological descriptions of dementia date back to very remote times, and today its study constitutes an enriching experience for medical practice. The aim of this Review is  to set out a historical overview of the emergence and evolution of the dementia syndrome, based on data supported by authorized and scientifically endorsed documentary sources. For this, a bibliographic search and analysis on the subject was carried out in the Scielo, Medline, LILCACS, ClinicalKey and HINARI databases. Strengthening the medical culture regarding dementia can promote a multidimensional approach in its diagnosis, with better results in the patient and family members' quality of life.